A 12-Mb Complete Coverage BAC Contig Map in Human Chromosome 16p13.1–p11.2 - Cao, Yicheng (Cold Spring Harbor Laboratory Press, 1999)
We have constructed a complete coverage BAC contig map that spans a 12-Mb genomic segment in the human chromosome 16p13.1–p11.2 region. The map consists of 68 previously mapped STSs and 289 BAC clones, 51 of which—corresponding to a total of 7.721 Mb of genomic DNA—have been sequenced, and provides a high resolution physical map of the region. Contigs were initially built based mainly on the analysis of STS contents and restriction fingerprint patterns of the clones. To close the gaps, probes derived from BAC clone ends were used to screen deeper BAC libraries. Clone end sequence data obtained from chromosome 16-specific BACs, as well as from public databases, were used for the identification of BACs that overlap with fully sequenced BACs by means of sequence match. This approach allowed precise alignment of clone overlaps in addition to restriction fingerprint comparison. A freehand contig drawing software tool was developed and used to manage the map data graphically and generate a real scale physical map. The map we present here is ∼3.5 × deep and provides a minimal tiling path that covers the region in an array of contigous, overlapping BACs.